Measuring Sustainability: Metrics And Methods In Green Analytical Chemistry - Nimushakavi, Suresh; A Ramkumar, A Ramkumar; Kumar, D. Sathis; E Jesudasan, Rajesh; Battu, Heera; K. Nithiyananthan, K. Nithiyananthan (Journal of Neonatal Surgery, 2025)
Green chemistry has emerged as a vital framework in laboratories, prioritizing sustainable, energy-efficient practices. The field focuses on replacing conventional methods with environmentally friendly alternatives by utilizing greener materials and improved waste management. Anastas first defined green chemistry, aiming to reduce hazardous substances, while also pioneering green analytical chemistry (GAC), which emphasizes practices like miniaturization and reagent substitution. This review highlights sustainable practices in analytical chemistry, focusing on techniques such as HPLC and UV-Visible Spectroscopy. Various metrics, including the National Environmental Methods Index (NEMI) and Analytical GREEnness (AGREE), are discussed to evaluate the eco-friendliness of these methods. The need for continuous improvement of these metrics is essential for researchers aiming to enhance sustainability in analytical practices, particularly in industries like pharmaceuticals and chemicals, where reducing environmental impact is crucial